Holding on to the good life: Samburu women's resilience and response to climate change - Walker, Sarah Elizabeth, author; Bruyere, Brett, advisor; Solomon, Jennifer, committee member; Skyelander, Kim, committee member; Zarestky, Jill, committee member (Colorado State University. Libraries, 2021)
This dissertation seeks to explore climate change resilience from the perspective of pastoral women in Samburu, Kenya. It investigates the resilience-related concepts of adaptive capacity, response strategies, and well-being. In Northern Kenya, the increasing frequency of drought is forcing pastoralists to respond to a changing climate while a variety of socioeconomic changes simultaneously both constrain and enhance their ability to respond. Pastoral women sit at the very nexus of these shifting dynamics; women continue to face significant barriers that limit their adaptive capacity, are often responsible for the increased workload associated with a changing climate, and experience unique and gendered impacts of engaging in climate change response strategies. The first manuscript in this dissertation applies a dimensional framework of well-being to the experiences and perspectives of Samburu women. We use semi-structured interviews and a novel participatory activity entitled "Build Your Best Life" to explore what it means for Samburu women to "have a good life." A well-being framework created by the ESRC Research Group on Well-Being in Developing Countries guides our presentation of twelve themes organized into three unique dimensions. Further, we argue for the importance of taking into account how different components of well-being influence each other and the implications of these interactions for climate resilience interventions. The second manuscript uses a participatory adaptation scenario and mapping activity to explore how formal education -- a common foundation of adaptive capacity -- influences Samburu women's livestock-related decision-making processes as they respond to drought. This manuscript builds on Cinner et al.'s (2018) framework of adaptive capacity and suggests that in order to leverage the potential of formal education to positively impact adaptive capacity, education must influence both the learning and agency components of adaptive capacity. Finally, the third manuscript investigates the influence of various response strategies on women's well-being and household livestock loss. We differentiate between coping and adaptation strategies and use the well-being framework from the first manuscript to look at how coping and adaptation uniquely impact women's sense of being able to provide for their children and their hope for the future. We use the gendered divisions of labour associated with drought adaptation and coping strategies to explain our results. As a whole, this dissertation attempts to understand how Samburu women are experiencing drought, the barriers they face in responding to drought, the response strategies they engage in, and how those responses may impact their well-being. Our results underscore the importance of using a gendered lens to understand climate resilience and creating culturally relevant frameworks for resilience-related concepts. We subsequently discuss implications for theory and practice.
Keywords: climate change; resilience; women; pastoralism; adaptation; well-being